Presenting Tantra Yoga: â€œThinkingâ€ to â€œBecoming-Womanâ€ for a Psycho-Ecology of Planetary Regeneration - Saxena, Neela Bhattacharya (Journal of Ecohumanism, 2022)
Europe and its influential knowledge systems are a late entry into the global marketplace of ideas, but they have had a far-reaching and, in many cases, devastating impact on our planet. Some Christian thinkers themselves now acknowledge that Anthropocene at least partially arose from an ego-centric reading of the Biblical narrative about Adamâ€™s domination over the natural world. We desperately need philosophers of air, water, fire, earth, and sky today, and we require those who can translate thought into praxis to help us find a way out of the crisis. Tantra as a mechanism and praxis has been elaborately developed by master yogis and yoginis. Â They created what can be called a psycho-ecology of our being where the macrocosm and microcosm meet in profound easeful love of life that can save us from our hungry-ghost-infested minds. Â This paper presents Tantra Yoga and its Gynocentric systems to contribute toward ecosophical praxis. Â